Factors hindering the implementation of augmented reality (AR) in Malaysian construction - Adibah, Danh Sapry (2017)
Augmented Reality (AR) technology has gaining a lot of attention in the construction industry on how it potentially helps in solving common problems in construction. The application of AR uses the concept of cyber-physical systems in which, it integrates digital information with the user's environment in real time, simply put, it uses the existing environment and overlays new information on top of it. The ability of AR in realistically visualize the end product of a construction project also eliminates the difficulties in handling dozen sets of 2D drawings. However, despites all the benefits AR can offer, the implementation of AR in Malaysian construction is still questionable. This paper discusses an overview of AR in construction field and the barrier factors in implementing this modern technology in Malaysian construction. The aims of this study are to determine the usage of technology in current practice and factors hindering the application of AR and finally, to address the main barrier of adopting AR in Malaysian construction. Semi-structured interviews and survey questionnaires were conducted to gather the possible barrier factors in implementing AR among the construction players. Then, by using Relative Importance Indices (RII) method, the collected data were analyzed. The overall results of the study indicate that the main barriers in implementing AR in Malaysian construction are lack of education on AR technology and unawareness about AR and its major enhancements to the project delivery process. In conclusion, to enable the progressive use of the technology, it is therefore important to address the actual factors hindering the implementation of AR in Malaysian construction.